The impact of patient and physician computer mediated communication skill training on reported communication and patient satisfaction. - Roter DL; Wexler R; Naragon P; Forrest B; Dees J; Almodovar A; Wood J (Patient Education & Counseling, 2012)
OBJECTIVE: The objective was to evaluate parallel patient and physician computer-mediated communication skill training on participants' report of skill use and patient satisfaction. METHODS: Separate patient and clinician web-tools comprised of over 500, 10-s video clips demonstrating patient-centered skills in various ways. Four clinician members of the American Academy of Family Physicians National Research Network participated by enrolling 194 patients into a randomized patient trial and 29 physicians into a non-randomized clinician trial of respective interventions. All participants completed baseline and follow-up self-report measures of visit communication and satisfaction. RESULTS: Intervention patients reported using more skills than controls in five of six skill areas, including identification of problems/concerns, information exchange, treatment adherence, shared decision-making and interpersonal rapport (all p<.05); post intervention, physicians reported using more skills in the same 5 areas (all p<.01). Intervention group patients reported higher levels of satisfaction than controls in five of six domains (all p<.05). CONCLUSION: Communication skill training delivered in a computer mediated format had a positive and parallel impact on both patient and clinician reported use of patient-centered communication and in patient satisfaction. PRACTICE IMPLICATIONS: Computer-mediated interventions are cost and time effective thereby increasing patient and clinician willingness to undertake training.